Estimasi Nilai Jasa Lingkungan Kawasan Hutan Dengan Tujuan Khusus (KHDTK) Aek Nauli Dengan Metode Travel Cost - Johansen Silalahi; Rospita Odorlina P. Situmorang; Endang Karlina (Inovasi, 2021)
From the aspect of ecotourism, Aek Nauli special forest purpose (KHDTK Aek Nauli) has potential to be developed as a gateway to Lake Toba Tourism. This study aims to determine the economic value of KHDTK Aek Nauli and to calculate the visiting cost of Aek Nauli KHDTK. The location of the study was KHDTK Aek Nauli located in Sibaganding Village, Simalungun Regency, North Sumatra. Estimated economic value of KHDTK Aek Nauli environmental services was carried out trough travel costs (Travel Cost Method). Data was collected from 73 respondents consisting of junior and senior high school students, college students and teachers. The economic value of the Special Purpose Forest Area Aek Nauli based on 2017 visit data was IDR. 4,073,628,200 per year. While the cost per visit according to the zoning area was around IDR. 31,084 to IDR.141,072 per visit / person / day ranging from 35-92 km from KHDTK Aek Nauli. This research suggests that the management of KHDTK Aek Nauli needs to review the enterance cost to the KHDTK which is currently very low in order to anticipate the impact of externalities and environmental damage due to increasing human activities in the forest area. Keywords: Economic value, KHDTK Aek Nauli, TCM, visitors